Efektifitas Metode Jal-Pin Al-Barqy Terhadap Ketrampilan Membaca Al-Qur’an Mahasiswa Fakultas Teknik: The Effectiveness of the Jal-Pin Al-Barqy Method on the Skills of Reading the Qur'an of Engineering Faculty Students - Farihah, Anis (Universitas Muhammadiyah Sidoarjo, 2017)
The blind of eradication the Qur'an for students of Universitas Muhammadiyah Sidoarjo that programs began to run in the last two years. That various programs continue to be used as a treatment for students who have not been able to read the Qur'an. The application of reading methode including the commonly Qur'an used in the Education the al-Barqy method. The idea of this research Jal-Pin al-Barqy as a capable of overcoming the inability of some students of the education character of Muhammadiyah (PKMU) in the Holy Qur'an, so this study aims to explore of Jal-Pin al-Barqy effectiveness of method in Qur'an recitation Students of Engineering Faculty which in fact is one of the Faculty with the highest number of students from other Faculties.The research using a quantitative correlation approach relationship between the Jal-Pin al-Barqy method and the final result of Qur'anic reading they were doing. When intertwined, then the possibility of using this method in the coming year can be maintained even sharpen.